10.13% Efficiency All‐Polymer Solar Cells Enabled by Improving the Optical Absorption of Polymer Acceptors. Issue 6 (30th April 2020) - Fan, Qunping; Ma, Ruijie; Liu, Tao; Su, Wenyan; Peng, Wenhong; Zhang, Ming; Wang, Zaiyu; Wen, Xin; Cong, Zhiyuan; Luo, Zhenghui; Hou, Lintao; Liu, Feng; et al.
Abstract : The limited light absorption capacity for most polymer acceptors hinders the improvement of the power conversion efficiency (PCE) of all‐polymer solar cells (all‐PSCs). Herein, by simultaneously increasing the conjugation of the acceptor unit and enhancing the electron‐donating ability of the donor unit, a novel narrow‐bandgap polymer acceptor PF3‐DTCO based on an A–D–A‐structured acceptor unit ITIC16 and a carbon–oxygen (C–O)‐bridged donor unit DTCO is developed. The extended conjugation of the acceptor units from IDIC16 to ITIC16 results in a red‐shifted absorption spectrum and improved absorption coefficient without significant reduction of the lowest unoccupied molecular orbital energy level. Moreover, in addition to further broadening the absorption spectrum by the enhanced intramolecular charge transfer effect, the introduction of C–O bridges into the donor unit improves the absorption coefficient and electron mobility, as well as optimizes the morphology and molecular order of active layers. As a result, the PF3‐DTCO achieves a higher PCE of 10.13% with a higher short‐circuit current density ( J sc ) of 15.75 mA cm −2 in all‐PSCs compared with its original polymer acceptor PF2‐DTC (PCE = 8.95% and J sc  = 13.82 mA cm −2 ). Herein, a promising method is provided to construct high‐performance polymer acceptors with excellent optical absorption for efficient all‐PSCs. Abstract : A narrow‐bandgap polymer acceptor PF3‐DTCO is developed by increasing the conjugation of the acceptor unit from the five‐ring‐fused IDIC16 to the seven‐ring‐fused ITIC16 and enhancing the electron‐donating ability of the donor unit from carbon‐bridged DTC to carbon–oxygen‐bridged DTCO, and a high power conversion efficiency of 10.13% with a high J sc of 15.75 mA cm −2 in all‐polymer solar cells is achieved.